A LEGAL ANALYSIS OF THE STATE OF EMERGENCY ON THE CLIMATE CRISIS AND MINING MANAGEMENT ON THE SMALL ISLAND OF SANGIHE AND ITS IMPLICATIONS FOR NATIONAL SECURITY - Muh. Jamil; M. Adnan Madjid; Anang Puji Utama (RADJA PUBLIKA, 2026)
Study This analyze relatedness between escalation crisis global climate , practices mining , and increasing vulnerability security Indonesian nationals on the islands small outermost with make the small island of Sangihe as studies case strategic . Crisis climate enlarge pressure ecological on the island small ones who have Power support limited at a time mark strategic for sovereignty and integrity of the country's maritime territory , especially when intersecting with mining scale big . Research This use method juridical normative through approach regulation legislation , conceptual , and analysis decision court For evaluate capacity law national in respond threat ecological and non - military findings show that Sangihe Island covering an area of ±73,700 hectares Once burdened concession mining of PT Tambang Mas Sangihe covering an area of ±42,000 hectares which triggered degradation environment , conflict social , and improvement risk climate . Although permission mining has canceled in a way powerful law remain in 2024, activity mine Keep going took place on an area of ±30 hectares by two companies local as proxy operation through scheme partnership with PT TMS. Framework law national , including ratification of the Paris Agreement, decision Supreme Court , and the Constitutional Court in particular consistent forbid mining on the island small with classify it as abnormally dangerous activity, emphasized that practice the is non- military threats to security national and demanding reconstruction policy integrated in situation emergency climate